L'art en France : 1945-1990. - Fondation Daniel Templon, Fréjus (Fréjus : Fondation Daniel Templon, 1990)
Adami, Valerio ; Alberola, Jean-Michel ; Alechinsky, Pierre ; Appel, Karel ; Arman ; Arp, Jean ; Balthus ; Barré, Martin ; Ben ; Bishop, James ; Blais, Jean-Charles ; Boltanski, Christian ; Braque, Georges ; Buffet, Bernard ; Buren, Daniel ; César ; Chaissac, Gaston ; Combas, Robert ; Dado ; Debré, Olivier ; Dubuffet, Jean ; Ernst, Max ; Etienne-Martin ; Fautrier, Jean ; Garouste, Gérard ; etc.
L'art en France : 1945-1990, Fondation Daniel Templon, Fréjus, 3 juillet - 16 septembre 1990
boek